The neural bases of discourse semantic and pragmatic deficits in patients with frontotemporal dementia and Alzheimer's disease. (July 2020) - Luzzi, Simona; Baldinelli, Sara; Ranaldi, Valentina; Fiori, Chiara; Plutino, Andrea; Fringuelli, Fabio M.; Silvestrini, Mauro; Baggio, Giosuè; Reverberi, Carlo
Abstract: Neuropsychological research on language has largely focused on how the brain processes single words and sentences whose meaning does not depend on the context or on the intentions of the speaker. Fewer studies have investigated the neurobiological bases of discourse semantics and pragmatics in patients and healthy individuals. We studied discourse semantic and pragmatic skills in patients with behavioral variant frontotemporal dementia (bvFTD) or Alzheimer's disease (AD) in comparison to healthy controls. Our goal was to assess whether and how the two patient groups differ in their cognitive and behavioral profiles, and whether these differences may be traced back to disease-specific patterns of neuronal hypometabolism. We combined PET imaging with standard neuropsychological assessment tools and a dedicated test battery designed to evaluate discourse semantics and pragmatics in patients with brain lesions or neurological disorders. We found that AD and bvFTD patients were both impaired compared to controls in discourse comprehension, but largely spared in single word comprehension. Importantly, we also found evidence for behavioral impairments specific to each disease, associated with different brain damage patterns. Compared to AD and controls, bvFTD patients had, behaviorally, more difficulty in evaluating whether certain inferences follow from discourse and in identifying humorous completions of stories; neurally, they had greater damage to medial and lateral regions of PFC. AD patients showed a different pattern of errors in a humor comprehension task than bvFTD patients and controls, and they showed greater posterior temporal and parietal cortical depletion. Both groups had comparable difficulties with understanding idioms and indirect requests. Finally, bvFTD-specific errors were correlated with the severity of hypometabolism in bvFTD. We discuss these results in light of previous research on the dementias as well as consequences for models of semantics and pragmatics in the brain.